Impact of conservative therapy on otologic signs and symptoms in patients with temporomandibular disorders: A systematic review and meta-analysis - de Medeiros Xavier, Geraldo Vinícius; Borges, Allya Francisca Marques; da Silva, Rayane Délcia; Coelho, Sônia Maria Aguiar; de Castro Corrêa, Camila [UNESP]; Santos, Rosane Sampaio; de Araujo, Cristiano Miranda; Stechman-Neto, José; Taveira, Karinna Veríssimo Meira (Taylor & Francis, 2024)
Objective: To evaluate the effect of conservative therapeutic interventions in adult patients with temporomandibular disorders (TMD) and associated otologic symptoms. Methods: An electronic search across six databases and grey literature was conducted. Studies were assessed for risk of bias, a random-effects meta-analysis, and the certainty of the evidence was evaluated using the GRADE tool. Results: Eighteen studies were included in the final synthesis. Otologic symptoms significantly decreased following intervention compared to baseline [OR = 0.09; 95% CI = 0.04 - 0.23, I² = 56%], reflecting an approximately 11-fold reduction in symptom likelihood of otologic symptoms after conservative treatment. Of the studies, eight had a low risk of bias, five had moderate, and four had high risk, with evidence certainty rated as very low. Conclusion: Conservative therapeutic interventions for TMD appear to reduce otologic symptoms. However, the certainty of the current evidence is limited, warranting further research to establish more definitive conclusions.
Keywords: conservative treatment; ear diseases; systematic review; Temporomandibular joint disorders